Hybrid approach using multi-criteria methods and mathematical programming for outsourcing logistic problem. (2018) - Bidani, Nesrine; Frikha, Hela Moalla
The decision maker can meet difficult decision problems in the presence of a multiple criteria. Indeed, the choice of a provider is a multi-criteria decision problem. This is the case of this paper which allows solving a logistics outsourcing problem based on multi-criteria decision aid. Several multi-criteria methods require a direct providing of parameters so that the decision maker obtains an alternatives ranking such as 'PROMETHEE' that is a method with multiple criteria. However, this task of direct and precise fixation of parameter values is quite difficult which poses the subjectivity problem of provided parameters. To reduce and overcome this problem, we propose a new multi-criteria approach which hybrids objective methods. However, this hybrid approach has some disadvantages. The results of the hybrid method are integrated in a mathematical program to choose a transport provider within the Tunisian Chemical Group (GCT) and determine the number of providers and optimal transported quantities.